Transformasi Kepemimpinan Kepala Sekolah dalam Pembinaan Karakter di SMA Averos Kota Sorong - udirman udirman; Nasaruddin Nasaruddin; Hamzah Hamzah; Muhammad Rusdi Rasyid (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2022)
The focus of this research is the leadership of the principal of Averos High School, Sorong City. The method used in this thesis is descriptive qualitative type, with a management and sociology approach, data collection instruments by means of interviews, observation and documentation, while data processing techniques by collecting data, reducing data, presenting, analyzing and drawing conclusions. The research results in this study are first, realizing the leadership of the school principal in carrying out character building by means of trustworthiness, uswatun hasanah, visioning, and a papuaan approach that is actualized in the principles of serving, decision, role model, responsibility, cooperation and change. Second, character development management, namely exemplary, habituation and advice that produces religious character, honesty, discipline, excellence, responsibility, love of the motherland, polite, caring, confident and scientific ethics. The third implementation includes management leadership, student achievement, and student behavior. The implications of this research will be a reference for schools in conducting character building both in Sorong and outside Sorong.